A–D–A‐type S, N‐Heteropentacenes: Next‐Generation Molecular Donor Materials for Efficient Vacuum‐Processed Organic Solar Cells. (22nd September 2014) - Mishra, Amaresh; Popovic, Dusko; Vogt, Astrid; Kast, Hannelore; Leitner, Tanja; Walzer, Karsten; Pfeiffer, Martin; Mena‐Osteritz, Elena; Bäuerle, Peter
<x xml:space="preserve">Abstract</x> A new class of acceptor‐substituted S, N‐heteropentacenes is developed for vacuum‐processed organic solar cells, providing encouraging power conversion efficiencies of up to 6.5%. Atomic force microscopy (AFM) investigations give a direct correlation between the blend film morphology and the photovoltaic parameters, such as short‐circuit current density (JSC) and fill factor (FF). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>